Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Untuk Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran IPAS Kelas V SD IT Insan Karim Samarinda Seberang - Risma Norma Dina; Nuri Nursandi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the application and effectiveness of the Think Pair Share (TPS) cooperative learning model in improving students' learning activeness in the IPAS subject at Grade V SD IT Insan Karim Samarinda Seberang. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 30 Grade V students. Data collection instruments included observation sheets, interviews, and documentation. The results showed a significant increase in students' learning activeness: from 50% in the pre-cycle, rising to 73.33% in Cycle I, and reaching 90% in Cycle II. With the achievement of the success indicator of at least 80% active students, it is concluded that the TPS learning model effectively improves students' learning activeness in the IPAS subject.